A Hospital Design Support System: Addressing Hospital Layout Design Challenges in China - Jia, Zhuoran (A+BE | Architecture and the Built Environment, 2025)
Hospitals are inherently complex systems, characterized by two distinct dimensions of complexity. First, from a functional perspective, medical procedures inside a hospital are complex. Second, from a spatial and organizational standpoint, hospitals resemble small urban environments, where corridors function as streets and spatial units operate similarly to distinct land uses within a city. This dual-layered complexity underscores the profound impact of hospital layout on users’ visibility and walkability within the hospital. Consequently, hospital design extends beyond mere architectural considerations; it entails the creation of a system where inefficiencies and risks can arise if not planned carefully. To enhance the design of the hospital system, we propose the integration of early operational insights into the design process through the development of a decision support system, referred to as the Hospital Design Support System (HDSS). The HDSS aims to establish a robust and transparent evaluation framework for systematically assessing hospital layout performance in terms of functionality and operational efficiency. This dissertation begins with an introduction chapter (chapter 1), which explains the rationales for developing an HDSS. It provides an overview of the research background, objectives, and research questions, while also defining relevant terminology, research scope, and the proposed methodology. Chapter 2 presents a comprehensive literature review, summarizing the key design challenges associated with hospital layout designs in China. These challenges include overcrowding, long patient waiting times, long patient walking distances, and difficulty in wayfinding. The proposed HDSS aims to address these issues through simulation modelling and exploratory network analysis. Since both approaches require a well-structured foundational dataset to function effectively, the development of such a dataset is a prerequisite for the HDSS. To meet this requirement, we introduce the Hospital Configuration Model (HCM), which serves as the foundational dataset for the HDSS. The HCM comprises four types of critical information: geometric, topological, semantic, and operational. Chapter 3 provides a detailed description of the HCM and outlines the methodology for systematically constructing it. Once the HCM is established, we can develop the HDSS to assess hospital layout configurations in relation to the four key design challenges. Chapter 4 describes the developed HDSS, which consists of three core models: a Four-Step Transportation Model which simulates the city-like characteristics of hospitals and evaluates hospital layout performance concerning overcrowding, patient walking distances, and difficulty in wayfinding; a Discrete-Event Simulation Model which captures the factory-like nature of hospitals and assesses hospital layout performance in terms of patient waiting times; and an Exploratory Network Analysis Model – unlike the previous two models, which focus on functional efficiency, this model evaluates the inherent logic of hospital spatial structures without considering the specific functions or attributes of hospitals’ spatial units. In other words, the Four-Step Transportation Model and the Discrete-Event Simulation Model assess the rational aspects of hospital layouts, while the Exploratory Network Analysis Model examines the irrational aspects of hospital layouts. Additionally, the HDSS includes an evaluation mechanism that translates simulation results into actionable insights to support informed decision-making. Specifically, disaggregated outputs from the simulation models are aggregated, normalized, and interpreted using a functional unit, ensuring fair comparisons across hospitals of varying scales. The HDSS serves as a robust decision-support tool for architects, hospital administrators, and head nurses during the early design stages, enabling the identification of optimal hospital layout alternatives. Finally, Chapter 5 presents the conclusion of this dissertation, addressing the research questions, summarizing key contributions, discussing research limitations, and suggesting potential directions for future studies.